Development of Interactive Learning Media Using Canva Application in IPAS Subject for Grade V at SDN 16 Sitiung - Putri, Dhara Atika; Ratnawati; Deri, Vivi Mutia (The Future of Education Journal, 2025)
This research was prompted by the limited learning media and the teachers at SDN 16 Sitiung not yet using engaging media in their IPAS (Science, Social Studies, and Arts) teaching process. Learning that incorporates media is crucial to support learning activities and achieve learning objectives. The purpose of this study was to develop interactive learning media using Canva to enhance the comprehension abilities of Class V students in IPAS at SDN 16 Sitiung, ensuring the media is valid, practical, and effective. The research method used in this study was Research and Development (R&D). The model employed was the ADDIE model, which consists of five phases: analysis, design, development, implementation, and evaluation. The validation results of the interactive learning media using Canva, assessed by six expert validators, obtained an average score of 87.53%, categorized as highly valid. The data analysis from the teacher response questionnaire, rated by one teacher, yielded an average of 95%, categorized as highly practical. Based on the student trial results, an average of 86.4% was achieved, also categorized as highly response practical. The effectiveness results of the learning assessment for Class V students obtained an average of 90.4%, categorized as highly effective. It can be concluded that the interactive learning media using Canva to enhance IPAS comprehension for Class V students at SDN 16 Sitiung can be declared valid, practical, and effective.